A Comparative Elastohydrostatic Analysis of CFV- and Capillary-Compensated Multirecess Hydrostatic/Hybrid Journal Bearing Operating with Micropolar Lubricant. (7th April 2013) - Verma, Suresh; Kumar, Vijay; Gupta, K. D.
Abstract : A comparative study on the performance characteristics of the flexible multirecess hydrostatic journal bearing system with constant flow valve and capillary restrictors has been presented considering the effect of micropolar parameters. The modified Reynolds equation for the flow of micropolar lubricant through the bearing has been solved using finite element method, and the resulting elastic deformation in the bearing shell has been determined iteratively. The results indicate that the micropolar parameters of the lubricant affect the performance of the flexible multirecess hydrostatic journal bearing system quite significantly.